Application of adaptor and load bar in car assembly / Khairul Nizam Ishak, Hairul Nizam Mohammad and Jamal Mohd - Ishak, Khairul Nizam; Mohammad, Hairul Nizam; Mohd, Jamal (1998)
We have selected this design because we wanted try to solve the problem that faced by Engineering Department Associated Motor Industries ( M ) , Shah Alam , Selangor Darul Ehsan and put into practice what we leam in three years in Mechanical Engineering. With our commitment, hardworking and advice from Mechanical Engineering Department, finally we have completed our project. What are we design is the important part in many of the assembly factory. Without this facilities, the cost of production may increase and the labor cost also higher. We hope this project can help the AMIM to solve the problem in future.